2014
DOI: 10.1007/s11356-014-3371-0
|View full text |Cite
|
Sign up to set email alerts
|

DDT and its metabolites are linked to increased risk of type 2 diabetes among Saudi adults: a cross-sectional study

Abstract: Organochlorine (OC) pesticides have recently been associated with type 2 diabetes in several non-Asian general populations. As there is currently an epidemic of type 2 diabetes mellitus in Asia. The prevalence and incidence of diabetes is increasing rapidly worldwide including many Arab Gulf countries. According to a community-based national epidemiological health survey, the overall prevalence of diabetes mellitus in Saudi adults (age group of 30-50 years) is 23.7%. A recent study by Al-Daghri et al. (BMC Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 40 publications
1
17
0
2
Order By: Relevance
“…Organochlorine pesticides like DDT are known to be such EDCs, and interfere with hormone signalling and metabolic pathways [ 5 , 38 , 39 ]. Levels of DDTs have been linked to type 2 diabetes and metabolic syndromes in people [ 40 , 41 ]. Involvement of the insulin-like growth factor-binding protein 1 (IGFBP1) has been demonstrated in insulin signaling in chickens [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Organochlorine pesticides like DDT are known to be such EDCs, and interfere with hormone signalling and metabolic pathways [ 5 , 38 , 39 ]. Levels of DDTs have been linked to type 2 diabetes and metabolic syndromes in people [ 40 , 41 ]. Involvement of the insulin-like growth factor-binding protein 1 (IGFBP1) has been demonstrated in insulin signaling in chickens [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Serum α-HCH, β-HCH, γ-HCH and δ-HCH levels were determined by gas chromatography–mass spectrometry (GC/MS) as described previously [ 20 ], with minor modifications. Each sample (0.5 mL of serum) was put into a 10 mL centrifuge tube.…”
Section: Methodsmentioning
confidence: 99%
“…Nowadays, DDT in human serum/plasma/blood commonly range between 1–500 nM [ 12 , 13 ] with maxima occasionally overcoming 1 μM [ 14 ]. Epidemiologic studies [ 15 18 ] showed a correlation between DDT in the human organism and the incidence of diabetes mellitus. Nevertheless, they did not specify if DDT affected insulin production by pancreatic beta-cells or insulin signaling in target tissues [ 7 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%